Maize insensitivity to culture filtrates from Exserohilum turcicum is related to quantitative resistance - Muñoz-Zavala, Carlos; Goodwin, Paul; Leyva Mir, Santos G.; Loladze, Alexander; Vargas-Hernández, Mateo; García‑León, Elizabeth; Tovar-Pedraza, Juan M.; San Vicente, Félix M.; Alakonya, Amos (Wiley, 2024)
Turcicum leaf blight (TLB) of maize is caused by Exserohilum turcicum. The TLB resistance is mainly associated with qualitative race-specific resistance that is linked to several Ht genes namely Ht1, Ht2, Ht3, HtM, HtN, HtNB and HtP. However, quantitative TLB resistance also occurs, but its mechanisms are poorly understood. In this study, tolerance or insensitivity to chlorosis and necrosis of E. turcicum culture filtrate was associated with quantitative TLB resistance. A novel detached maize seedling assay was developed for E. turcicum culture filtrate using methanol-treated modified Fries medium. Screening of E. turcicum isolates of races 2, 3, 23, 3 N, 23 N and 123 N against 61 maize inbred lines with diverse levels of resistance to TLB was conducted in the greenhouse by fungal inoculation and the detached seedling culture filtrate assay. Using an isolate of race 123 N, which can overcome all the qualitative resistance genes, a simple linear regression model (R-2 = 0.68, p = .90) for the 61 inbred lines was established between disease severity from foliar inoculations and culture filtrate symptom rating of the detached seedling assay. Two maize lines CML474 and CML483 had relatively high culture filtrate symptom ratings but very low disease severity with foliar inoculation indicating that these sources of quantitative TLB resistance may be unrelated to tolerance to E. turcicum culture filtrates, whose effect on seedlings could be due to the toxin known as HT-toxin or monocerin.